Epidemiology and treatment of psoriasis: a Chinese perspective - Pan R; Zhang JZ (Dove Medical Press, 2014)
Ran Pan, Jianzhong Zhang Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of China Background: Psoriasis is a chronic inflammatory skin disease that has a negative impact on quality of life. Prevalence and management of psoriasis varies among different ethnic groups. Objectives: To evaluate the epidemiology and treatment of psoriasis from a Chinese perspective. Methods: A systematic search was performed on PubMed and the China National Knowledge Infrastructure using the following MeSH terms: "psoriasis" and ("prevalence" or "epidemiology") and "risk factor" and ("management" or "treatment"). The search included all citations from 1975 to 2013. Data were sorted by prevalence, age of onset, sex distribution, type, severity, risk factors, and management and treatment. Severity of psoriasis was classified as mild, moderate, or severe. The studies cited in this review involved Chinese subjects. Results: The prevalence of psoriasis in the People's Republic of China ranged from 0.11% to 0.47%. Genetic and environmental factors played an important role in initiation and exacerbation of psoriasis. Results showed that psoriasis can occur at any age but is more common in young and middle-aged individuals and occurs more often in men and earlier in women. Psoriasis vulgaris accounted for 82.6%–97.1% of psoriasis patients. More than 90% of patients with psoriasis were classified as mild or moderately severe. Risk factors are numerous. Management and treatment was based on classification level. Conclusion: The prevalence of psoriasis in Chinese patients is lower than that in Caucasians. A cold and dry climate, bacterial infection, diet, and stress are important risk factors for developing psoriasis. There are a variety of management and treatment options available. As such, Chinese patients with psoriasis can receive effective, safe, and individualized treatment. Keywords: psoriasis, epidemiology, risk factors, treatment